An Insight on the Geometry of the Golden Ratio - Adhikari, Iswar Mani (INTELLIGENCE Journal of Multidisciplinary Research, 2024)
Mathematics has a strong logical interconnection with structural design and architecture. Ratios are good examples of their interconnectivity. Nature is attractive due to the proper ratios of various components in them and between others. In nature, trees, forests, leaves, flowers, fruits, Himalayas, hills, valleys, springs, rivers, lakes, etc. show a rhythmic balance and seem harmonic and aesthetically pleasing. The golden ratio is considered the most pleasing to human visual sensation not limited only to aesthetic beauty but also found prominently in the natural world and is a fascinating topic. It can be constructed in different ways depending on the geometrical structures preferred. In this paper, our focus is on the geometry of the golden ratio.